Molecular Characterization of L. monocytogenes Isolated From Milk and Milk Products - Warke, Shubhangi Rambhau (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A total of 194 (121 bovine milk samples and 73 milk products) were screened for Listeria monocytogenes. The isolation was attempted by two-step enrichment procedure in UVM-1 and UVM- 2 broths followed by plating on DRIA. The isolates were confirmed by biochemical test and in-vitro PI-PLC pathogenicity test. The L. monocytogenes isolates from milk and milk products were also tested for virulenceassociated genes plcA, hlyA, actA, and iap by multiplex polymerase chain reaction (PCR). Prevalence of L. monocytogenes found to be 15.70% and 10.95% in milk and milk products, respectively. The PCR profile of L. monocytogenes isolates revealed variation in the presence of the virulence-associated genes namely plcA, hlyA, actA, and iap. Four L. monocytogene isolates from milk samples and two isolates from milk products revealed PI-PLC activity. L. monocytogenes isolates were sensitive to ampicillin, penicillin, ciprofloxacin and vancomycin